معالم في النقل الديداكتيكي لدرس التربية الإسلامية: Didactic Transfer of Islamic Education - Amiri, Abou El Kacem; Iskandi, Iskandi; Fitrahadi, Agung (MEDIOVA: Journal of Islamic Media Studies, 2024)
The article addresses the problems related to the didactic transmission of the Islamic education lesson, and presents a theoretical conception of this delicate process, accompanied by some applications. It paves the way for this perception by highlighting the importance of didactic transport, its motives, purposes and foundations. To conclude by proposing an applied conception of this process at the level of classroom practice. The article concludes the need for didactic transfer of knowledge and educational values to ensure the success of the educational learning process and its freedom from complexity and ambiguity for the learner. يعالج المقال الإشكالات المتعلقة بالنقل الديداكتيكي لدرس التربية الإسلامية، ويقدم تصورا نظريا لهذه العملية الدقيقة، مشفوعا ببعض التطبيقات. ويمهد لهذا التصور من خلال إبراز أهمية النقل الديداكتيكي ودوافعه ومقاصده وأسسه. لينتهي إلى اقتراح تصور تطبيقي لهذه العملية على مستوى الممارسة الفصلية. ليخلص المقال إلى ضرورة النقل الديداكتيكي للمعارف والقيم التربوية لضمان نجاح العملية التعليمية التعلمية وخلوها من التعقيد والغموض لدى المتعلم.